2016
DOI: 10.1002/jso.24461
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of liver resection for patients with four or more colorectal liver metastases has not improved in the era of modern chemotherapy

Abstract: The prognosis of patients with ≥4 CRLM that undergo liver resection has not improved despite the development of modern chemotherapies. J. Surg. Oncol. 2016;114:959-965. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Although previous studies reported worse OS of RSC after liver resection for CRLM [9-12], the result focused on metachronous liver metastasis has not been reported yet. Moreover, the surgical indication and treatment strategy for CRLM were standardized in the present study [20][21][22]. Therefore, the results of the present study might be more reliable.…”
Section: Discussionmentioning
confidence: 98%
“…Although previous studies reported worse OS of RSC after liver resection for CRLM [9-12], the result focused on metachronous liver metastasis has not been reported yet. Moreover, the surgical indication and treatment strategy for CRLM were standardized in the present study [20][21][22]. Therefore, the results of the present study might be more reliable.…”
Section: Discussionmentioning
confidence: 98%
“…CEA levels ≥ 5.0 ng/mL have an adverse effect on survival that is independent of tumor stage [ 7 - 9 ]. Hokuto et al [ 10 ] reported that a serum CEA level of ≥ 20 ng/mL was one of the prognostic factors for DFS in patients with ≥ 4 colorectal liver metastases and a systematic review assessing prognostic factors for patients undergoing lung metastasectomy showed that a prethoracotomy associated elevation in CEA level was associated with poor survival [ 11 ]. In this study, elevated preoperative CEA level was identified to be an independent risk predictor for oncologic outcomes, which is consistent with the prior results in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Patient management. The operative procedure and perioperative management have been reported previously (21)(22)(23)(24). Hepatic parenchymal resection was performed with a clamp crushing technique, and an intermittent Pringle maneuver was used for almost all cases.…”
Section: Methodsmentioning
confidence: 99%